IPTEKS BAGI MASYARAKAT (IBM) PEMBUATAN SABUN KESEHATAN KULIT - Rise Desnita; Sri Luliana (Universitas Muhammadiyah Pontianak, 2017)
Science for Society (IbM) is a program of dedication to society funded by Research and Technology Directorate of Higher Education. Ibm Leather Health Soap Making proposed by the group of Lecturers Prodi Pharmacy Faculty of Medicine UNTAN aims to help the first partner of Bidikmisi Student Enterprises Group of Pharmaceutical Technology in terms of improving skills in processing natural ingredients into skin health soap preparations. IbM proponents help provide business capital, provide guidance on making skin health soap and provide information on how to apply for permission to circulate skin health soap products. In addition, the proposer of IbM also provides pharmacy management consultancy according to the growing pharmacoeconomics and their pharmacy business will grow better in the future. The result of training, mentoring and guidance to Bidikmisi Student Enterprises Group of Pharmaceutical Technology run well and smoothly. The publication of IbM's Leather Health Soap Program publication seminar held for pharmacy students and open to the public. The hope of the seminar is the students and the general public can get knowledge about the manufacture of soap, cosmetic business opportunities such as soap and soap product registrations so that the future in West Kalimantan can appear business actors in the field of skin health soap products.Keywords: Soap, Health, Skin, IbM